Alcoholic beverage consumption, smoking habits, and periodontitis: A cross‐sectional investigation of the NutriNet‐Santé study. Issue 5 (18th September 2020) - Hamdi, Zeineb; Detzen, Laurent; Fessi, Sabrine; Julia, Chantal; Hercberg, Serge; Czernichow, Sébastien; Boillot, Adrien; Touvier, Mathilde; Bouchard, Philippe; Andreeva, Valentina A.; Carra, Maria Clotilde
Abstract: Background: Recent evidence suggests that dietary habits influence the development and severity of periodontitis. The present cross‐sectional study evaluated the association between different types and quantity of alcoholic beverage consumption (alone and interacting with smoking) and the probability to suffer from severe periodontitis in the French e‐cohort NutriNet‐Santé. Methods: The study population consisted of 35, 390 adults (mean age: 49.04 ± 13.94 years), who filled oral health questionnaires and completed at least three non‐consecutive 24‐hour dietary records. Data on type and frequency of alcoholic beverage consumption were obtained from a semi‐quantitative self‐reported alcohol frequency questionnaire; the daily quantity (g/day) was estimated from the 24‐hour dietary records. The probability of severe periodontitis (main dependent variable) was assessed by calculating the modified periodontal screening score (mPESS) from selected questions. Results: A total of 7263 individuals (20.5%) presented a high probability of suffering from severe periodontitis (high‐mPESS). After adjusting for confounding factors, the frequency of alcoholic beverage consumption was significantly higher among high‐mPESS group than their low‐mPESS counterparts, especially for hard liquor/spirits (1.9 ± 1.4 days/week for high‐PESS versus 1.6 ± 1.1 days/week the low‐PESS [ P < 0.0001]). The mean daily quantity of ethanol was also higher in high‐mPESS versus low‐mPESS individuals (11.2 ± 15.6 versus 7.9 ± 12.3 g/day; P = 0.011). A stronger association with self‐report severe periodontitis was noted when alcohol consumption exceeding > 20 g/day for women and > 30 g/day for men was combined with smoking habit (OR = 7.30 [95% CI: 6.1‐8.73]). Conclusion: The present results support an association between alcoholic beverage consumption and self‐report severe periodontitis, particularly when it is associated with current smoking.